Musket, Map and Money: How Military Technology Shaped Geopolitics and Economics - Teng, Jimmy (De Gruyter, 2013)
Waves of military technological changes have swept through the Eurasian land mass since the dawn of civilization. Military technological changes decisively shaped geopolitics and the fortunes of states, empires and civilizations. In his book Jimmy Teng claims that to understand the impacts of these military technological changes is in fact to understand the causes behind the following major historical puzzles or important facts: the leading position of the Near East during the dawn of civilization; the splendid achievements of Greece, India and China during the axial era; the classical golden age of India under the Gupta Empire; the Abbasid Golden Age of the Islamic world and the Sung Puzzle of China during the medieval era; and the rise of the West during the early modern and modern era.